Tradução e adaptação transcultural da escala de avaliação da primeira infância para bebês e crianças DECA I/T (Devereux Early Childhood Assessment for Infants And Toddlers) - Coelho, Mônica Andrigo Moreira de Ulhoa (2017)
The subject of this master´s dissertation is related to early childhood and resilience in infants (four weeks to 18 months old) and toddlers (18 to 36 months old). The study aimed at translating into Portuguese and transculturally adapting the early childhood assessment for infants and toddlers named ―Devereux Early Childhood Assessment for Infants and Toddlers‖ (DECA I/T), developed by Gregg Powell, Mary Mackrain and Paul LeBuffe, owned by The Devereux Foundation, edited and published by Kaplan Early Learning Corporation in 2007. DECA I/T assessment measures the social and emotional protective factors (attachment/relationship, initiative and self-regulation) to evaluate and indicate the strength of such factors in infants and toddlers. For the translation and transcultural adaptation of the assessment, the guidelines of Hambleton and Patsula (1998) and Souza and Rojjanasrirat (2010) were generally used. The procedure consisted of the following steps: (a) translation of the original instrument in English into Portuguese by two Brazilian, bilingual, independent translators, being one of them a sworn-translator, both of them familiarized with the Brazilian and American cultures, and without knowledge in Psychology; (b) comparison and consolidation of both translated versions by the researcher, who acted as a third translator, and review of the synthetized version; (c) back-translation of the consolidated version in Portuguese into English by another American, bilingual, independent translator, fluent in Portuguese, familiarized with the Brazilian and American cultures and not working in the Psychology area, followed by review and approval of the final version of the assessment in Portuguese by an Expert Committee; (d) application of the Portuguese final version in a pilot project. The translated DECA I was applied to and responded by 13 evaluators (six mothers, one grandmother, one father and five nursery caregivers of infants). A total of 12 infants were evaluated (one of them was evaluated by the father and the nursery caregiver). The translated DECA T was applied to and responded by 13 evaluators (six mothers, one grandmother, two room assistants, two educators e two teachers of toddlers). A total of 19 toddlers were evaluated (two room assistants evaluated two toddlers each, two educators evaluated three toddlers each, and two teachers evaluated three toddlers each). After application of the pilot project, the translation into Portuguese of DECA I/T was considered culturally adapted and apt for future validation